Analysis of Dual Heat Sources in a Partially Open Enclosure. (2nd May 2013) - McGarry, M.; Kohl, James G.
Abstract : In this study a partially open enclosure with two heat sources is examined to determine the Nusselt number along the hot wall. The first part of the study examines the effect of the Rayleigh number ratio on the Nusselt number. The largest Rayleigh number ratio results in the highest magnitude of the Nusselt number. The second part of the study examines what happens to the Nusselt number along the hot wall as the Rayleigh number ratio for the two blocks is different. This situation can arise when the two blocks have unequal heat source values. The largest Nusselt numbers correspond to the situation when the block along the top wall has a Rayleigh number ratio that is ten times higher than the Rayleigh number ratio for the block along the hot wall. The largest Nusselt number magnitudes can be attributed to the strong vortex in the corner near the hot wall.